Depiction of Lakulisa inside a niche on the Lalatabimba - Temples of India Project Team (Jio Institute, 2024)
A depiction of Lakulisa, a preceptor of the doctrine of the Pashupata tradition of Shaivism, is found inside a niche on the lalatabimba (lintel). Seated in padmasana (lotus pedestal pose), he holds a danda (staff) and phala (fruit) and wears a yajnopavita (sacred thread).